Influence of Boundary Conditions on Deformation and Stresses of a Cooled Piston in Diesel Engine - Wladyslaw Mitianiec (Advanced Aspects of Engineering Research Vol. 4, 2021)
The chapter presents influence of boundary conditions on mechanical and thermal stresses of an oil cooled piston in diesel engine Scania DC09074A and its deformation due to high combustion pressure and changeable temperature. Due to different fixing of the pin in the piston hub the deformation of the piston shape and von Misses stresses differ at the same boundary conditions. The piston is an indirect element in heat exchange in combustion engines, because it transfers the heat from the gas to cylinder walls by piston rings and some part of heat is transferred from the bottom surfaces of the piston to the gas inside the crankcase. Calculations of the piston loads were carried out by using 0D mathematical model at assumption of the Wiebe combustion model and the Woschni heat transfer model for homogenous mixture. For precise determination of the gas temperature in the combustion chamber the CFD technique was used and for that case the simulation of compression, combustion and expansion processes was carried out by using the program Fluent. The numerical calculations were done for two kinds of fuel: diesel oil and CNG. For proper work of CNG engine the compression ratio was decreased. This was done by reducing the volume of the combustion chamber. Calculations done in the program Ansys showed that the modification of the piston do not influence significantly on the total stresses. The chapter shows the differences of the total stresses and piston deformation at fastened piston hub and at “floating” piston pin. Most calculations are made at assumption that the piston hubs are fixed, but it is not right assumption. In summary the paper gives indications how to set boundary conditions for “floating” piston pin. Due to different fixing of the pin in the piston hub the deformation of the piston shape and von Misses stresses differ at the same boundary conditions The analysis has shown that FEM calculations of the piston should be done together with the pin for giving the engineers right information how to design the piston shape, usually “barrel-oval”, in order to enable a proper clearance between the piston and cylinder walls particularly at high loads.